Evaluation of the required level of l-lysine amino acid in the diet of Gilan native ducks up to the age of 7 weeks - Ghorab, M. Jamili; Shahryar, H. Aghdam; Ebrahimnezhad, Y.; Farahvash, T.; Vahdatpour, T.; Ghorbani, A. (Frontiers in Animal Science, 2025)
The present study aimed to determine the dietary lysine (Lys) requirements of Gilan native ducks (mallards) up to seven weeks of age. A total of 300 male ducklings were randomly assigned to five dietary treatments with six replicates of ten birds each, in a completely randomized design. Birds received 0.7, 0.8, 0.9, 1.0, and 1.1% lysine during the starter phase (1–14 days) and 0.45, 0.55, 0.65, 0.75, and 0.85% lysine during the grower phase (15–49 days). The results showed that during the starter phase, feed intake (FI) and body weight gain (BWG) significantly increased, and feed conversion ratio (FCR) decreased in ducks fed 1.0% and 1.1% lysine compared to the National Research Council recommended level (0.9%) (P<0.05). In the grower phase, ducks receiving 0.75% lysine showed enhanced FI and BWG, while those fed 0.85% lysine demonstrated improved FCR (P<0.05). Higher lysine levels had no significant effect on spleen, bursa of fbricius, or breast weight, crypt diameter, villus height, heterophile percentage, H/L ratio, monocyte count, MCHC, glutathione peroxidase activity, or Newcastle antibody titer (P>0.05). However, lysine levels ≥0.65% significantly increased thigh and wing weights, glucose, cholesterol, HDL, LDL, total protein, albumin, uric acid, hematological indices (hematocrit, RBC, WBC, hemoglobin, lymphocytes, MCH, MCV, eosinophils), crypt depth, villus thickness, and superoxide dismutase activity (P<0.05). In contrast, ducks receiving 0.45% lysine exhibited higher liver and intestinal weights, triglyceride, urea, and VLDL levels (P<0.05). In conclusion, lysine levels above National Research Council recommendations improved growth performance, carcass characteristics, serum biochemical indices, and intestinal morphology in Gilan native ducks. Based on these results, dietary lysine levels of 1.0–1.1% during the starter phase and 0.75–0.85% during the grower phase are recommended for optimal performance.